Postnatal changes of vesicular glutamate transporter (VGluT)1 and VGluT2 immunoreactivities and their colocalization in the mouse forebrain - Kouichi Nakamura; Hiroyuki Hioki; Fumino Fujiyama; Takeshi Kaneko (2005)
Abstract Vesicular glutamate transporter 1 (VGluT1) and VGluT2 accumulate neurotransmitter glutamate into synaptic vesicles at presynaptic terminals, and their antibodies are thus considered to be a good marker for glutamatergic axon terminals. In the present study, we investigated the postnatal development and maturation of glutamatergic neuronal systems by single‐ and double‐immunolabelings for VGluT1 and VGluT2 in mouse forebrain including the telencephalon and diencephalon. VGluT2 immunoreactivity was widely distributed in the forebrain, particularly in the diencephalon, from postnatal day 0 (P0) to adulthood, suggesting relatively early maturation of VGluT2‐loaded glutamatergic axons. In contrast, VGluT1 immunoreactivity was intense only in the limbic regions at P0, and drastically increased in the other telencephalic and diencephalic regions during three postnatal weeks. Interestingly, VGluT1 immunoreactivity was frequently colocalized with VGluT2 immunoreactivity at single axon terminal‐like profiles in layer IV of the primary somatosensory area from P5 to P10 and in the ventral posteromedial thalamic nucleus from P0 to P14. This was in sharp contrast to the finding that almost no colocalization was found in glomeruli of the olfactory bulb, patchy regions of the caudate‐putamen, and the ventral posterolateral thalamic nucleus, where moderate to intense immunoreactivities for VGluT1 and VGluT2 were intermingled with each other in neuropil during postnatal development. The present results indicate that VGluT2‐loaded glutamatergic axons maturate earlier than VGluT1‐laden axons in the mouse telencephalic and diencephalic regions, and suggest that VGluT1 plays a transient developmental role in some glutamatergic systems that mainly use VGluT2 in the adulthood. J. Comp. Neurol. 492:263–288, 2005. © 2005 Wiley‐Liss, Inc.